(untitled) - Boller, Paul F. (Chicago, 1969)
The book gives to the history of this transition in thought in the Gilded Age every bit of the narrative movement, the zest, action, and human agony expected of the best social or political histories. This is a book about American ideas in the gilded Age, that is, in the period roughly from the end of the Civil War to the end of the Spanish-American War.
Keywords: United states; History